Influência da contaminação por Trypanosoma cruzi (Kinetoplastida: Trypanosomatidae) na espermatogênese de Triatomíneos (Hemiptera: Reduviidae) - Pereira, Nathália Paiva [UNESP] (2015)
The insects of the Triatominae, also known as barbers, have a great importance in human parasitology, as are vectors of Trypanosoma cruzi protozoan that causes Chagas disease. In addition to medical and health importance, these insects stand out in cytogenetics, due to peculiar characteristics as holocentric chromosomes, and an unusual meiosis, in which the autosomes segregate regularly, while the sex chromosomes present the first equational division and the second reductive. In addition, several studies are conducted to identify the effects of physiological stress in the body of these insects. However, there are no studies evaluating the influence of contamination of insects Trypanosoma cruzi in the reproduction of these individuals. For this, we analyzed the cytogenetic characteristics during spermatogenesis three triatomine species: Triatoma brasiliensis, Rhodnius neglectus and Panstrongylus megistus, which were infected in the laboratory with T. cruzi. Later blades were made with the testicles of these insects and stained by conventional cytogenetic technique and performed cell counts to quantitatively determine these cells in the testes. It was possible to observe an increase in cell size of polyploid nuclei, nutritional cells present in the seminiferous tubules and all cells during spermatogenesis, plus a disruption in nuclear and nucleolar during cell division. Furthermore, there was a decrease in cell quantities given infected individuals, an increase in the number of polyploid cells and nuclei in interphase, and a decrease in cell division. These changes may be due to physiological stress that infection with T. cruzi caused to the body of these insects. In addition, cells in interphase and early chromosome condensation had higher heteropycnotic corpuscles in contaminated than in those who were free of protozoan that causes Chagas disease showing that the physiological stress organisms may be the main reason for this change in...